Enhancing security and capacity in FSO transmission for next-generation networks using OFDM/OCDMA-based ICSM codes - Abd El-Mottaleb, Somia A.; Singh, Mehtab; Alshathri, Samah; El-Shafai, Walid; H. Aly, Moustafa (Frontiers in Physics, 2023)
In order to address the growing demands for both enhanced security levels and increased transmission capacity, this research proposes a novel approach for free space optic (FSO) transmission. The proposed design incorporates an Identity Column Shift Matrix (ICSM) code to ensure robust security. Additionally, capacity enhancement is achieved through the utilization of a 4-level Quadrature-Amplitude Modulation (4-QAM) scheme in conjunction with an Orthogonal Frequency Division Multiplexing (OFDM) modulator. The performance of the system is evaluated across three channels, each transmitting data at a rate of 20 Gb/s, while operating in an FSO channel that is subject to varying atmospheric attenuation effects and atmospheric turbulence. Real meteorological data from three different cities (Alexandria: Egypt, Jeddah: Kingdom of Saudi Arabia (KSA), and Hyderabad: India), situated across two continents, are incorporated to demonstrate the practicality of implementing the proposed model in real-world environments. The experimental results reveal that an increase in atmospheric turbulence leads to a higher Bit Error Rate (BER) and lower Received Optical Power (ROP), resulting in degraded data reception. Furthermore, the study examines the impact of weather conditions, indicating that the longest and shortest propagation ranges of 12.5 km and 0.286 km, respectively, are achieved under clear weather and heavy dust storms. These conditions yield an ROP of -9.5 dBm and a log(BER) of approximately -2.5. Conversely, in the presence of strong turbulence, the performance further deteriorates. The proposed model demonstrates its ability to transmit a message signal over a distance of 0.8375 km, with a log(BER) of -2.6 under weak atmospheric turbulence. However, under strong atmospheric turbulence at the same distance, the log(BER) increases to -0.5. Regarding specific cities, the FSO range for transmitting information signals is found to be 9.58 km in Jeddah, which decreases to 6.58 km in Alexandria and 5.17 km in Hyderabad due to increased atmospheric attenuation in these cities.